Protection of Social Rights as a Permament Challenge for the European Union - Ryszka, Joanna (Review of European and Comparative Law, 2021)
Social rights protection in the European Union has undergone significant development. Currently their protection is regulated by relevant treaty provisions and the Charter of Fundamental Rights (Charter), both of a primary law nature, as well as by the non-binding European Pillar of Social Rights (Pillar). The aim of the paper is the assessment of the social rights protection in the EU, and whether all social rights provided in the CFR have their counterparts in the EPSR, hence whether and in what way the EPSR assists the actual exercise of social rights provided by the CFR. Comparing the content of the above-mentioned legal instruments makes it possible to answer the question whether all social rights provided in the Charter have their counterparts in the Pillar. This can help determine whether the latter affects the implementation of the former. If the answer is in the affirmative, it can further allow for determining in what way the principles of the Pillar assist in the actual exercise of social rights provided by the Charter. This is very important taking into account the need for an ongoing response to unforeseen threats, like for example COVID-19. The social aspects of EU integration thus are and will remain a subject of interest in the nearest future.